Surgical Treatment of Degenerative Disk Disease in Three Scandinavian Countries: An International Register Study Based on Three Merged National Spine Registers. Issue 8 (December 2019) - Andersen, Mikkel Østerheden; Fritzell, Peter; Eiskjaer, Søren Peter; Lagerbäck, Tobias; Hägg, Olle; Nordvall, Dennis; Lönne, Greger; Solberg, Tore; Jacobs, Wilco; van Hooff, Miranda; Gerdhem, Paul; Gehrchen, Martin
Study Design: Observational study of prospectively collected data. Objectives: Patients with chronic low back pain resistant to nonoperative treatment often face a poor prognosis for recovery. The aim of the current study was to compare the variation and outcome of surgical treatment of degenerative disc disease in the Scandinavian countries based on The International Consortium for Health Outcomes Measurement core spine data sets. Methods: Anonymized individual level data from 3 national registers were pooled into 1 database. At the time of surgery, the patient reports data on demographics, lifestyle topics, comorbidity, and data on health-related quality of life such as Oswestry Disability Index, Euro-Qol-5D, and back and leg pain scores. The surgeon records diagnosis, type of surgery performed, and complications. One-year follow-ups are obtained with questionnaires. Baseline and 1-year follow-up data were analyzed to expose any differences between the countries. Results: A total of 1893 patients were included. At 1-year follow-up, 1315 (72%) patients responded. There were statistically significant baseline differences in age, smoking, comorbidity, frequency of previous surgery and intensity of back and leg pain. Isolated fusion was the primary procedure in all the countries ranging from 84% in Denmark to 76% in Sweden. There was clinically relevant improvement in all outcome measures except leg pain. Conclusions: In homogenous populations with similar health care systems the treatment traditions can vary considerably. Despite variations in preoperative variables, patient reported outcomes improve significantly and clinically relevant with surgical treatment.